1999
DOI: 10.1023/a:1009289414832
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Antioxidant properties of selenium producing a protective barrier against free radicals play an important role in numerous metabolic and immunologic processes associated with oxidation-reduction reactions which take place during intracellular digestion of phagocyted bacteria. The aim of our study was to examine the properties of an organic compound of selenium, 4-(o-tolilo)-selenosemicarbazide of p-chlorobenzoic acid in terms of its retention in organs, effect on erythropoesis and phagocytic abilities of neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…420 According to this model, the reason for the predictable enantioselectivity arises from the subtilisin template, which catalyzes the esterification or acylation of racemic alkyl aryl alcohols or amines, respectively. 423 The enantioselectivity of subtilisin for (S)-configured alkyl arylamines (486, 487, Figure 64) or alcohols (488,489) has been associated with the arrangement of substrate-binding pockets S 1 and S 1 ′. [423][424][425] In selenosubtilisin BPN′ enzyme, the residues Glu 156 and Gly169 are located in the S 1 pocket and the third residue, Tyr 217, is part of the S 1 ′ pocket.…”
Section: Synthetic Peptides Enzymes and Catalytic Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…420 According to this model, the reason for the predictable enantioselectivity arises from the subtilisin template, which catalyzes the esterification or acylation of racemic alkyl aryl alcohols or amines, respectively. 423 The enantioselectivity of subtilisin for (S)-configured alkyl arylamines (486, 487, Figure 64) or alcohols (488,489) has been associated with the arrangement of substrate-binding pockets S 1 and S 1 ′. [423][424][425] In selenosubtilisin BPN′ enzyme, the residues Glu 156 and Gly169 are located in the S 1 pocket and the third residue, Tyr 217, is part of the S 1 ′ pocket.…”
Section: Synthetic Peptides Enzymes and Catalytic Antibodiesmentioning
confidence: 99%
“…The main trends of the selenium studies concern their most suitable chemical forms, toxicity limits, and their effects on the immunological mechanisms . The importance of selenium in AIDS-related viruses has been described. Apart from certain selenosemicarbazides and other inorganic selenium species, a number of organoselenium compounds have been described as potential immunostimulants and inducers of interferon γ (INF-γ) and other cytokines. Inglot et al reported that ebselen and related compounds induce INF-γ and tumor necrosis factor (TNF) in human peripheral blood leukocytes (PBL) .…”
Section: Compounds With Other Biological Activitiesmentioning
confidence: 99%